A new visual feedback-based system for the assessment of pinch force, endurance, accuracy and precision. A test-retest reliability study. (June 2021) - Dottor, Alberto; Camerone, Eleonora; Job, Mirko; Barbiani, Diletta; Frisaldi, Elisa; Testa, Marco
Introduction: Given that pinch is a precision grip involved in sustained submaximal activities, a Sustained Contraction (SC) task could be associated to Maximal Voluntary Contraction (MVC). To better evaluate the thumb-index system, the test-retest reliability of pinch MVC and SC, measured by a visual feedback-based pinch gauge was assessed. Methods: 26 healthy participants performed MVC and SC in two separate sessions. SC required to maintain 40%MVC as long as possible and it was evaluated in terms of time, accuracy (Mean Distance between force trace and target force, MD), precision (Coefficient of Variability of force trace, CV). MD and CV analyses were conducted dividing the SC task into three equivalent time stages (beginning, middle, exhaustion). Relative Reliability (RR) was measured by Intraclass Correlation Coefficient, and Absolute Reliability (AR) was measured by Standard Error of Measurement and by Bland-Altman plot. Results: MVC and Time showed high RR and AR in both hands. RR of MD and CV in right hand was excellent in the beginning and middle stages, and fair in the exhaustion one, showing decreasing reliability as fatigue increases. In the left hand RR of MD and CV was generally lower. MD showed excellent reliability in the beginning stage and good reliability in the other stages. CV showed fair relative reliability at both beginning and middle stages, excellent in the last one. Conversely, it was observed high AR of MD and CV in all stages in both hands. Conclusions: All indices are reliable to assess motor control of thumb-index pinch in both hands.